Modified phosphate-based positive electrode material, preparation method and application thereof

By coating the surface of phosphate-based cathode materials with a composite of organic thermoelectric polymers and n-type thermoelectric dopants, the problems of insufficient conductivity and lithium-ion mobility were solved, thereby improving battery performance and simplifying processing.

CN117673349BActive Publication Date: 2026-11-06SHENZHEN DYNANONIC CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311750331.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2026-11-06
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

Phosphate-based cathode materials have poor conductivity and lithium-ion mobility, resulting in poor battery performance. Existing carbon coating methods suffer from inhomogeneity and processing performance issues.

Method used

An organic charge transfer complex formed by coating an organic thermoelectric polymer and an n-type thermoelectric dopant onto the surface of a phosphate-based active core forms a DA-type conjugated structure, which improves electron and ion mobility and simplifies the preparation process.

Benefits of technology

It improves the conductivity and ion mobility of the cathode material, enhances the uniformity and compactness of the shell, simplifies the processing, and improves the charge and discharge capacity and coulombic efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117673349B_ABST
    Figure CN117673349B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery materials, and particularly relates to a modified phosphate-based positive electrode material and a preparation method and application thereof. The modified phosphate-based positive electrode material comprises a phosphate-based active core and a shell layer coated on the outer surface of the core, and the shell layer comprises an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant. The organic thermoelectric polymer comprises an electron-withdrawing conjugated unit and an electron-donating unit, and the electron-withdrawing conjugated unit comprises an alkoxy-substituted chain. The modified phosphate-based positive electrode material is coated and modified by the organic charge transfer complex formed by the organic thermoelectric polymer and the n-type thermoelectric dopant in the shell layer, and has the characteristics of good coating effect, high compaction density, high electrical conductivity and ion transference rate, and good structural and electrochemical performance stability, which is beneficial to improving the electrochemical performance such as the charge-discharge capacity and coulombic efficiency of the positive electrode material applied to the battery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery materials technology, and in particular relates to a modified phosphate-based cathode material, its preparation method and application. Background Technology

[0002] Lithium-ion batteries consist of four parts: positive and negative electrode materials, electrolyte, and separator. Among these, the positive electrode material plays a decisive role in the overall cost, weight, and performance of the battery. Compared to other lithium-ion battery positive electrode materials such as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), and ternary materials like lithium nickel cobalt manganese oxide (LiMnO2), lithium lithium cobalt manganese oxide (LiMnO2)... x Ni y Co z O2), etc., with lithium iron phosphate (LiFePO4, LFP) and lithium manganese iron phosphate (LiMn) materials. x Fe 1-x Phosphate-based cathode materials, represented by PO4 (LMFP), have received widespread attention and application over the past decade due to their advantages such as low cost, excellent safety performance, and good cycle performance. In recent years, they have been widely used in electric vehicles and energy storage.

[0003] However, phosphate-based cathode materials such as lithium iron phosphate and lithium manganese iron phosphate exhibit very poor conductivity and lithium-ion mobility, approaching insulator levels, which increases the polarization of the material within the battery. This leads to insufficient battery capacity and affects battery safety. To improve this, carbon coating is currently used to enhance conductivity, typically by high-temperature sintering to coat the carbon source onto the surface of phosphate-based cathode material particles. However, carbon coating not only makes the material surface prone to moisture adsorption and results in uneven coating, but its effectiveness in improving the ionic and electronic conductivity of phosphate-based cathode materials also needs further refinement, negatively impacting the processing and electrical properties of phosphate-based cathode materials. Summary of the Invention

[0004] The purpose of this application is to provide a modified phosphate-based cathode material, its preparation method, and its application, aiming to solve, to some extent, the problem of poor ionic and electronic conductivity of phosphate-based cathode materials.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0006] In a first aspect, this application provides a modified phosphate-based cathode material, comprising a phosphate-based active core and a shell coating the outer surface of the core, wherein the shell comprises an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant; wherein the organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains.

[0007] In the modified phosphate-based cathode material of this application, an organic charge transfer composite is coated on the outer surface of the phosphate-based active core. This organic charge transfer composite is formed by an organic thermoelectric polymer and an n-type thermoelectric dopant. The organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, forming a D (electron-donating unit) - A (electron-withdrawing unit) type conjugated interaction structure, which enhances intermolecular forces and increases the carrier mobility of the organic thermoelectric polymer. Furthermore, it improves the conductivity of the shell composite material. In addition, the electron-withdrawing conjugated units contain alkoxy-substituted chains, which have stronger ion mobility. These substitution chains further effectively improve the conductivity and ion mobility of the organic thermoelectric polymer, while also improving the compatibility between the organic thermoelectric polymer and the n-type thermoelectric dopant, achieving better doping effects and improving the electronic / ionic conductivity and stability of the shell composite material. Furthermore, the n-type thermoelectric dopant in the shell organic charge transfer composite forms a complex with the organic thermoelectric polymer, enabling electrons in the shell to transfer from the highest occupied orbital (HOMO) of the dopant to the lowest unoccupied orbital (LUMO) of the polymer, thus completing charge transfer. This effectively improves the electron migration effect in the cathode material, resulting in higher conductivity of the modified phosphate-based cathode material. On another front, both the organic thermoelectric polymer and the n-type thermoelectric dopant forming the organic charge transfer composite in the shell of the modified phosphate-based cathode material are organic compounds. These not only exhibit good bonding with the core phosphate-based active material, improving the uniformity, consistency, and tightness of the shell coating and thus increasing the compaction density of the cathode material, but also eliminate the need for further carbonization, simplifying the preparation process and improving processing performance.

[0008] Secondly, this application provides a method for preparing a modified phosphate-based cathode material, comprising the following steps:

[0009] Provides phosphate-based active particles;

[0010] A coating material is provided, the coating material comprising an organic charge transfer complex formed of an organic thermoelectric polymer and an n-type thermoelectric dopant, wherein the organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains;

[0011] After mixing phosphate-based active particles and coating materials in the liquid phase, the solvent is removed, allowing the coating material to coat the outer surface of the phosphate-based active particles to form a shell, thus obtaining a modified phosphate-based cathode material.

[0012] This application describes a method for preparing a modified phosphate-based cathode material. The method involves providing phosphate-based active particles and a coating material comprising an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant. The two are then mixed in a liquid phase to ensure thorough mixing and doping of the components in the coating material, which then coat the surface of the phosphate-based active particles. The solvent is removed, allowing the coating material to form a shell on the outer surface of the phosphate-based active particles. This ensures uniformity and consistency of the coating material on the outer surface of the phosphate-based active particles, resulting in the modified phosphate-based cathode material. The preparation process is simple. Coating through liquid-phase mixing and solvent removal effectively improves the uniformity and consistency of the coating, which is beneficial for increasing the material's compaction density. The resulting modified phosphate-based cathode material, modified by the organic charge transfer complex formed by the organic thermoelectric polymer and n-type thermoelectric dopant in the shell, exhibits good coating effect, high compaction density, high conductivity and ion mobility, and good structural and electrochemical stability. This is beneficial for improving the charge-discharge capacity and coulombic efficiency of the cathode material when applied to battery systems.

[0013] Thirdly, this application provides a secondary battery in which the positive electrode sheet contains the modified phosphate-based positive electrode material described above or the modified phosphate-based positive electrode material prepared by the above method.

[0014] The secondary battery of this application contains the above-mentioned modified phosphate-based positive electrode material in its positive electrode sheet. This modified phosphate-based positive electrode material is modified by a shell coating containing organic thermoelectric polymers and n-type thermoelectric dopants on its surface. It has the characteristics of good coating effect, high compaction density, high conductivity and ion mobility, and good structural and electrochemical performance stability, thus improving the electrochemical performance of the secondary battery, such as charge and discharge capacity and coulombic efficiency. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic flowchart of the preparation method of the modified phosphate-based cathode material provided in the embodiments of this application;

[0017] Figure 2These are XRD test images of the modified phosphate-based cathode materials provided in Examples 1-3 and Comparative Example 1 of this application;

[0018] Figure 3 These are XRD test images of the modified phosphate-based cathode materials provided in Example 7 and Comparative Examples 2-3 of this application;

[0019] Figure 4 This is a SEM image of the uncoated lithium iron phosphate obtained in step ① of Embodiment 1 of this application;

[0020] Figure 5 This is a SEM image of the modified lithium iron phosphate cathode material provided in Example 1 of this application;

[0021] Figure 6 This is a SEM image of the modified lithium iron phosphate cathode material provided in Example 2 of this application;

[0022] Figure 7 This is a SEM image of the modified lithium iron phosphate cathode material provided in Example 3 of this application;

[0023] Figure 8 This is a SEM image of the modified lithium iron phosphate cathode material provided in Example 7 of this application;

[0024] Figure 9 This is a SEM image of the modified lithium iron phosphate cathode material provided in Comparative Example 1 of this application;

[0025] Figure 10 This is a SEM image of the modified lithium iron phosphate cathode material provided in Comparative Example 2 of this application;

[0026] Figure 11 This is a SEM image of the modified lithium iron phosphate cathode material provided in Comparative Example 3 of this application;

[0027] Figure 12 These are charge-discharge curves at 0.1C after the modified phosphate-based cathode materials provided in Examples 1-3 and Comparative Example 1 of this application are applied to lithium-ion batteries.

[0028] Figure 13 These are charge-discharge curves at 1C after the modified phosphate-based cathode materials provided in Examples 1-3 and Comparative Example 1 of this application are applied to lithium-ion batteries.

[0029] Figure 14 These are charge-discharge curves at 0.1C after the modified phosphate-based cathode materials provided in Example 7 and Comparative Examples 2-3 of this application are applied to lithium-ion batteries.

[0030] Figure 15These are charge-discharge curves at 1C after the modified phosphate-based cathode materials provided in Example 7 and Comparative Examples 2-3 of this application are applied to lithium-ion batteries. Detailed Implementation

[0031] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0032] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0033] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0034] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0035] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0036] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass mentioned in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.

[0037] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0038] The first aspect of this application provides a modified phosphate-based cathode material, comprising a phosphate-based active core and a shell coating the outer surface of the core. The shell comprises an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant. The organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains.

[0039] In the modified phosphate-based cathode material provided in the first aspect of this application, an organic charge transfer composite shell formed by an organic thermoelectric polymer and an n-type thermoelectric dopant is coated on the outer surface of the phosphate-based active core. The organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, forming a D (electron-donating unit) - A (electron-withdrawing unit) type conjugated interaction structure, which enhances intermolecular forces and increases the carrier mobility of the organic thermoelectric polymer; it also improves the electrical conductivity of the shell composite material. Furthermore, the electron-withdrawing conjugated units contain alkoxy-substituted chains, which have stronger ion mobility. These substitution chains further effectively improve the electrical conductivity and ion mobility of the organic thermoelectric polymer, while also improving the compatibility between the organic thermoelectric polymer and the n-type thermoelectric dopant, achieving better doping effects and improving the electronic / ionic conductivity and stability of the shell composite material. Furthermore, the n-type thermoelectric dopant in the shell organic charge transfer composite forms a complex with the organic thermoelectric polymer, enabling electrons in the shell to transfer from the highest occupied orbital (HOMO) of the dopant to the lowest unoccupied orbital (LUMO) of the polymer, thus completing charge transfer. This effectively improves the electron migration effect in the cathode material, resulting in higher conductivity of the modified phosphate-based cathode material. On another front, both the organic thermoelectric polymer and the n-type thermoelectric dopant forming the organic charge transfer composite in the shell of the modified phosphate-based cathode material are organic compounds. These not only exhibit good bonding with the core phosphate-based active material, improving the uniformity, consistency, and tightness of the shell coating, which is beneficial for increasing the compaction density of the cathode material, but also eliminate the need for further carbonization, simplifying the preparation process and improving processing performance. Therefore, the modified phosphate-based cathode material possesses characteristics such as good coating effect, high compaction density, high conductivity and ion mobility, and good structural and electrochemical stability, which are beneficial for improving the charge-discharge capacity and coulombic efficiency of the cathode material when applied to battery systems.

[0040] In some possible implementations, the modified phosphate-based cathode material also includes free organic charge transfer complexes. During the coating process of the modified phosphate-based cathode material in this application, some free organic charge transfer complexes inevitably exist. These free organic charge transfer complexes outside the particles, including organic thermoelectric polymers and n-type thermoelectric dopants, can also play a role in conducting lithium ions, improving the electrochemical performance of the cathode material, such as conductivity and ion migration ability.

[0041] In some possible implementations, the electron-withdrawing conjugated units in the organic thermoelectric polymer include at least one of 4,9-dibromonaphthalenediimide, pyrrolopyrroledione, isoindigo, benzodifurandione, and thiopheneimide; these electron-withdrawing conjugated units are all capable of accepting electrons and have electron-withdrawing groups, which can promote the release of electrons from the donor and acceptor system in the organic thermoelectric polymer, thereby enhancing the electron-accepting ability of the donor and acceptor system and improving the conductivity of the organic thermoelectric polymer.

[0042] In some possible implementations, the alkoxy-substituted chains in the electron-withdrawing conjugated units of this application include at least one of polyethylene glycol ether-based substituted chains and polyethylene glycol ester-based substituted chains. These alkoxy-substituted chains all have high ion mobility, which can further improve the conductivity and ion mobility of the organic thermoelectric polymer, and at the same time improve the compatibility of the organic thermoelectric polymer with the n-type thermoelectric dopant, thereby achieving a better doping effect.

[0043] In some possible implementations, the alkoxy-substituted chain includes a polyethylene glycol methyl ether substituted chain. At least one of them; these alkoxy substitution chains can better improve the electrical conductivity and ion migration ability of organic thermoelectric polymers, while improving the compatibility of organic thermoelectric polymers with n-type thermoelectric dopants, and achieving better doping and coating effects on the outer surface of the phosphate-based active core.

[0044] In some possible implementations, the number of repeating units of ethylene glycol in the alkoxy-substituted chain is 3 to 12. In this case, the chain length of the alkoxy-substituted chain is beneficial to improving the conductivity and ion migration ability of the organic thermoelectric polymer, while also ensuring that the organic thermoelectric polymer has good solubility and ensuring the compatibility and interdoping effect between the organic thermoelectric polymer and the n-type thermoelectric dopant.

[0045] In some possible implementations, the electron-donating units in the organic thermoelectric polymer include at least one of the following: bithiophene units, bisthiophene units, thiophene units, selenophene units, and furan units. These electron-donating units can all provide electrons and form a DA-type conjugated structure with the electron-withdrawing conjugated units, forming DA interactions, improving intermolecular forces, increasing the carrier mobility of the material, enhancing the ability of the organic thermoelectric polymer to accept electrons, and improving the conductivity of the organic thermoelectric polymer, thereby improving the conductivity of the modified phosphate-based cathode material.

[0046] In some possible implementations, electron-withdrawing conjugated units and electron-donating units alternately repeat in the organic thermoelectric polymer; that is, a DA-type conjugated structure with alternating electron-donating units (D) and electron-deficient units (A) is formed, which can better improve intermolecular forces, improve the ionic and electronic conductivity of the organic thermoelectric polymer, and thus improve the conductivity of the modified phosphate-based cathode material.

[0047] In some possible implementations, the organic thermoelectric polymer includes polypyrrolopyrrole dione with alkoxy-substituted chains. Polybisthiophene imide containing alkoxy-substituted chains Polyisodigofera tinctoria containing alkoxy-substituted chains Polynaphthalimide materials containing alkoxy-substituted chains At least one of the following. These organic thermoelectric polymers all contain strong electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains with high ion migration efficiency. Therefore, these organic thermoelectric polymers all have high ionic and electronic conductivity, which can improve the ion and electron migration efficiency of modified phosphate-based cathode materials and improve the electrochemical performance of cathode materials after coating.

[0048] In some possible implementations, the number-average molecular weight of the organic thermoelectric polymer is 70 kDa to 100 kDa. In this case, the organic thermoelectric polymer with this number-average molecular weight has both high electrical conductivity and can form a better coating effect on the surface of the phosphate-based active core.

[0049] In some possible implementations, the n-type thermoelectric dopant includes 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole. At least one of (N-DMBI), cobalt dicene, and ruthenium dicene. These dopants all possess excellent n-type conductivity, i.e., electronic conductivity. The shell layer is formed by a combination of mechatronic polymer and n-type thermoelectric dopant, which enables electrons to transfer from the highest occupied orbital (HOMO) of the dopant to the lowest unoccupied orbital (LUMO) of the polymer, thereby improving electron transfer efficiency. The conductivity of the doped shell composite material reaches a high level, which further improves the conductivity of modified phosphate-based cathode materials.

[0050] In some possible implementations, the mass ratio of the organic thermoelectric polymer to the n-type thermoelectric dopant in the shell is 1:(0.07–0.2). This results in a better composite doping effect between the organic thermoelectric polymer and the n-type thermoelectric dopant in the shell, improving the ionic and electronic conductivity of the coated modified phosphate-based cathode material. Simultaneously, it enhances the compatibility between the organic thermoelectric polymer and the n-type thermoelectric dopant, ensuring uniform coating, density, and stability, and improving the compaction density, capacity, and stability of the modified phosphate-based cathode material. For example, the mass ratio of the organic thermoelectric polymer to the n-type thermoelectric dopant in the shell can be 1:0.07, 1:0.08, 1:0.1, 1:0.12, 1:0.15, 1:0.18, 1:0.2, or any value between 1:(0.07–0.2).

[0051] In some possible implementations, the shell layer in the modified phosphate-based cathode material comprises 3.3% to 4.4% by mass. In this case, it is ensured that the organic thermoelectric polymer and n-type thermoelectric dopant in the shell layer form a uniform, consistent, dense, and complete coating layer for the phosphate-based active core. This ensures both effective improvement in the conductivity and electrochemical performance, such as capacity, of the modified phosphate-based cathode material. For example, the mass percentage of the shell layer in the modified phosphate-based cathode material can be 3.3%, 3.4%, 3.5%, 3.8%, 4.0%, 4.2%, 4.4%, or any value between 3.3% and 4.4%.

[0052] In some possible implementations, the shell thickness in the modified phosphate-based cathode material is 3 nm to 5 nm. In this case, the shell thickness provides a complete, uniform, and stable coating of the phosphate-based active core, improving the electrochemical properties of the modified phosphate-based cathode material, such as conductivity. For example, the shell thickness in the modified phosphate-based cathode material can be 3 nm, 4 nm, 5 nm, or any value between 3 nm and 5 nm.

[0053] In some possible implementations, the D50 particle size of the modified phosphate-based cathode material is 500 nm to 2 μm. In this case, the smaller particle size of the modified phosphate-based cathode material shortens the ion migration path, which is beneficial for ion insertion and extraction during charge and discharge, thus improving the rate performance and other electrochemical properties of the modified phosphate-based cathode material. For example, the D50 particle size of the modified phosphate-based cathode material can be 500 nm to 800 nm, 800 nm to 1000 nm, 1 μm to 1.2 μm, 1.2 μm to 1.5 μm, 1.5 μm to 1.8 μm, 1.8 μm to 2.0 μm, etc.

[0054] In some possible implementations, the modified phosphate-based cathode materials include at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium nickel phosphate as the phosphate active core. These phosphate-based cathode materials possess abundant lithium-ion storage sites, providing high specific capacity. They also exhibit high safety and long lifespan, strong adaptability, high energy density, low cost, long driving range, and good low-temperature performance, making them promising for applications in the new energy field. Furthermore, coating modification with organic thermoelectric polymers and n-type thermoelectric dopants can effectively improve ionic and electronic conductivity, further enhancing the electrochemical performance of the cathode material.

[0055] The modified phosphate-based cathode material described in the above embodiments of this application can be prepared by the methods described in the following embodiments.

[0056] Secondly, embodiments of this application provide a method for preparing a modified phosphate-based cathode material, as shown in the attached figure. Figure 1 As shown, it includes the following steps:

[0057] S10. Provides phosphate-based active particles;

[0058] S20. Provide a coating material comprising an organic charge transfer complex formed of an organic thermoelectric polymer and an n-type thermoelectric dopant, wherein the organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains;

[0059] S30. After mixing the phosphate-based active particles and the coating material in the liquid phase, the solvent is removed so that the coating material coats the outer surface of the phosphate-based active particles to form a shell layer, thereby obtaining a modified phosphate-based cathode material.

[0060] The second aspect of this application describes a method for preparing a modified phosphate-based cathode material. This method involves providing phosphate-based active particles and a coating material comprising an organic charge transfer complex formed from an organic thermoelectric polymer and an n-type thermoelectric dopant. The two are then mixed in a liquid phase to ensure thorough mixing and doping of the components in the coating material, which then coat the surface of the phosphate-based active particles. The solvent is removed, allowing the coating material to form a shell on the outer surface of the phosphate-based active particles. This ensures the uniformity and consistency of the coating material on the outer surface of the phosphate-based active particles, resulting in a modified phosphate-based cathode material. The preparation process is simple. Coating via liquid-phase mixing and solvent removal effectively improves the uniformity and consistency of the coating, which is beneficial for increasing the compaction density of the material. The modified phosphate-based cathode material obtained is modified by coating with an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant in the shell. It has the characteristics of good coating effect, high compaction density, high conductivity and ion mobility, and good structural and electrochemical performance stability, which is beneficial to improving the electrochemical performance of the cathode material when applied to battery systems, such as charge and discharge capacity and coulombic efficiency.

[0061] In step S10 above, phosphate-based active particles are provided. In some possible implementations, this includes the following steps: obtaining each raw material component according to the stoichiometric ratio of each element in the phosphate-based active material, mixing and grinding them to form a powdered precursor; then, calcining the precursor in an inert atmosphere such as nitrogen or argon to obtain phosphate-based active particles. The stoichiometric ratio can be the molar ratio of the elements or the mass ratio converted from the molar ratio. In some embodiments, the calcination conditions include heating at a heating rate of 3°C / min to 8°C / min to a constant temperature of 520°C to 560°C for 2 to 5 hours, followed by heating at a heating rate of 3°C / min to 8°C / min to a constant temperature of 720°C to 780°C for 8 to 12 hours.

[0062] In some possible implementations, phosphate-based active particles include at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium nickel phosphate. These phosphate-based cathode materials possess abundant lithium-ion storage sites, providing high specific capacity. They also exhibit high safety and long lifespan, strong adaptability, high energy density, low cost, long driving range, and good low-temperature performance, making them promising for applications in the new energy field. In this case, the raw material components for preparing phosphate-based active particles include lithium sources, iron sources, manganese sources, vanadium sources, nickel sources, and phosphorus sources.

[0063] In some embodiments, the phosphate-based active material includes lithium iron phosphate, and its preparation includes the steps of mixing and grinding a lithium source, an iron source and a phosphorus source with a main element molar ratio of 1:1:1, and then calcining the mixture to obtain lithium iron phosphate active particles.

[0064] In some embodiments, the phosphate-based active material includes lithium manganese iron phosphate, the preparation of which includes the steps of: mixing and grinding a lithium source, an iron source, a manganese source and a phosphorus source in a main element molar ratio of 1:(0.1~0.9):(0.1~0.9):(0.81~1.07), and then calcining the mixture to obtain lithium manganese iron phosphate active particles.

[0065] In some possible implementations, the lithium source is at least one of inorganic lithium salts or organic lithium salts. Specifically, the lithium source includes at least one of lithium oxide, lithium carbonate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium citrate. The iron source is at least one of inorganic iron salts, ferrates, or organic iron salts. Specifically, the iron source includes one or more of ferric nitrate, ferrous sulfate, ferric citrate, ferrous oxalate, ferric oxide, and ferrous phosphate. The manganese source is at least one of inorganic manganese salts, manganate, or organic manganese salts. Specifically, the manganese source includes at least one of MnO2, Mn(NO3)2, MnSO4, and Mn3(PO4)2·3H2O. The phosphorus source is at least one of inorganic phosphates or organic phosphates. Specifically, the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate, and ferric phosphate.

[0066] In step S20 above, a coating material comprising an organic thermoelectric polymer and an n-type thermoelectric dopant is provided. In some possible implementations, the preparation of the organic thermoelectric polymer includes the following steps: In an inert atmosphere, an electron-withdrawing conjugated monomer, an electron-donating monomer, a catalytic system, and an organic solvent are mixed and heated to obtain the organic thermoelectric polymer. The heating reaction causes the electron-withdrawing conjugated monomer and the electron-donating monomer to combine, forming a DA-type conjugated structure with alternating electron-donating units (D) and electron-deficient units (A), thus obtaining the organic thermoelectric polymer. The inert atmosphere includes nitrogen, argon, helium, etc.

[0067] In some possible implementations, the molar ratio of electron-withdrawing conjugated monomers to electron-donating monomers is 1:(1.0–1.2); in this case, it is possible to sufficiently ensure the reaction between the electron-withdrawing conjugated monomers and electron-donating monomers to form an organic thermoelectric polymer with a DA-type conjugated structure. A slight excess of electron-donating monomers is beneficial to ensuring sufficient reaction.

[0068] In some possible implementations, the catalytic system includes a metal catalyst, a catalyst complexing agent, an alkali metal salt, and pivalic acid. The catalyst complexing agent can complex with the metal catalyst, maximizing its catalytic effect. The alkali metal salt, as a basic substance, works with the pivalic acid to ensure the smooth progress of the entire catalytic reaction cycle.

[0069] In some embodiments, the metal catalyst includes at least one palladium catalyst selected from tris(benzylacetone)dipalladium, palladium chloride, and palladium acetate. In some embodiments, the catalyst complexing agent includes at least one phosphine ligand selected from tris(o-methoxyphenyl)phenylphosphine, tris(o-methylphenylphosphine), and triphenylphosphine. In some embodiments, the alkali metal salt includes cesium carbonate and / or potassium carbonate. In some embodiments, the mass ratio of the metal catalyst, catalyst complexing agent, alkali metal salt, and additive in the catalytic system is (15–20) mg : (120–160) mg : (1–3) g : (80–120) mg.

[0070] In some possible implementations, the heating reaction is carried out at a temperature of 110°C to 120°C for 24 to 48 hours; under these conditions, the reaction between electron-withdrawing conjugated monomers and electron-withdrawing monomers can be adequately ensured.

[0071] In some possible implementations, the organic solvent used in the step of preparing the organic thermoelectric polymer includes at least one of o-dichlorobenzene, toluene, xylene, and chlorobenzene. These organic solvents have good dissolution and dispersion effects on electron-withdrawing conjugated monomers, electron monomers, and catalytic systems, which is conducive to the combination of electron-withdrawing conjugated monomers and electron monomers to form an alternating electron-donating unit (D) and electron-deficient unit (A) DA-type conjugated structure, thus obtaining the organic thermoelectric polymer.

[0072] In some embodiments, the preparation of the organic thermoelectric polymer includes the following steps: adding an electron-withdrawing conjugated monomer and an electron-withdrawing monomer in a 1:1 ratio to a reaction vessel, followed by the addition of 5% palladium catalyst, 20% phosphine ligand, 3 equivalents of cesium carbonate, and 1 equivalent of terpentine. Toluene (0.1M concentration) is then added under a nitrogen or argon atmosphere. The reaction system is heated to 110°C–120°C at a heating rate of 2°C / min–5°C / min and reacted at this temperature for 24–48 hours. After cooling, the reaction solution is added to methanol to precipitate the product. After filtration, the product is dried in a 45°C oven for 12 hours to obtain the organic thermoelectric polymer.

[0073] In some possible implementations, the preparation steps of the coating material include: dissolving an organic thermoelectric polymer and an n-type thermoelectric dopant in an organic solvent under an inert atmosphere, and then mixing them at a temperature of 65℃ to 85℃ for 0.5 hours to 2 hours to obtain the coating material. In this case, the solution environment ensures sufficient mixing between the organic thermoelectric polymer and the n-type thermoelectric dopant, forming a cross-doped organic charge transfer composite coating material. This organic charge transfer composite can better improve the electrochemical performance, such as conductivity, of the modified phosphate-based cathode material. The inert atmosphere includes nitrogen, argon, helium, etc.

[0074] In some possible implementations, the organic solvent used in the step of preparing the coating material includes at least one of o-dichlorobenzene, toluene, xylene, and chlorobenzene; these organic solvents have good dissolution and dispersion effects on both organic thermoelectric polymers and n-type thermoelectric dopants, which is beneficial for the mixed doping between organic thermoelectric polymers and n-type thermoelectric dopants.

[0075] In some embodiments, under a nitrogen or argon atmosphere, the organic thermoelectric polymer is dissolved in o-dichlorobenzene (concentration 5-10 g / L), and an n-type thermoelectric dopant (concentration 5-10 g / L) is added. The mixture is then stirred at a temperature of 65°C-85°C for 0.5-2 hours to obtain the coating material. This method allows for better interdoping between the organic thermoelectric polymer and the n-type thermoelectric dopant, which is beneficial for the subsequent formation of a uniform, consistent, dense, and stable shell on the surface of the phosphate-based active material.

[0076] In some possible implementations, the electron-withdrawing conjugated units in the organic thermoelectric polymer include at least one of the following: 4,9-dibromonaphthalenediimide unit, pyrrolopyrroledione unit, isoindigo unit, benzodifurandione unit, and thiopheneimide unit. These electron-withdrawing conjugated monomers are all capable of accepting electrons and possess electron-withdrawing groups, which can promote the release of electrons from the donor-acceptor system in the organic thermoelectric polymer, thereby enhancing the electron-acceptor system's ability to accept electrons and thus improving the electrical conductivity of the organic thermoelectric polymer.

[0077] In some possible implementations, the alkoxy-substituted chain includes at least one of polyethylene glycol ether-based substituted chains and polyethylene glycol ester-based substituted chains. These alkoxy-substituted chains all have high ion mobility, which can further improve the conductivity and ion mobility of the organic thermoelectric polymer, while also improving the compatibility of the organic thermoelectric polymer with n-type thermoelectric dopants, thus achieving better doping effects.

[0078] In some possible implementations, the alkoxy-substituted chain includes at least one of polyethylene glycol methyl ether substituted chains having a repeating number of 3 to 12 ethylene glycol units. These alkoxy-substituted chains can better improve the electrical conductivity and ion migration ability of the organic thermoelectric polymer, while improving the compatibility of the organic thermoelectric polymer with n-type thermoelectric dopants, and achieving a better doping coating effect on the outer surface of the phosphate-based active core.

[0079] In some possible implementations, the electron-donating units in the organic thermoelectric polymer include at least one of the following: bithiophene units, bisthiophene units, thiophene units, selenophene units, and furan units. These electron-donating monomers can all donate electrons, forming a DA-type conjugated structure with the electron-withdrawing conjugated units, thus creating DA interactions. This enhances intermolecular forces, increases the carrier mobility of the material, strengthens the electron-accepting ability of the organic thermoelectric polymer, and improves the conductivity of the organic thermoelectric polymer, thereby increasing the conductivity of the modified phosphate-based cathode material.

[0080] In some possible implementations, the organic thermoelectric polymer includes at least one of the following: polypyrrolopyrrole dione with alkoxy-substituted chains, polybisthiophene imide with alkoxy-substituted chains, polyisoindigo with alkoxy-substituted chains, and polynaphthalene diimide with alkoxy-substituted chains. These organic thermoelectric polymers all contain strong electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains with high ion migration efficiency. Therefore, these organic thermoelectric polymers all possess high ionic and electronic conductivity, thereby improving the ion and electron migration efficiency of the modified phosphate-based cathode material after coating, and enhancing the electrochemical performance of the cathode material.

[0081] In some possible implementations, the number-average molecular weight of the organic thermoelectric polymer is 70 kDa to 100 kDa. In this case, the organic thermoelectric polymer with this number-average molecular weight has both high electrical conductivity and can form a better coating effect on the surface of the phosphate-based active core.

[0082] In some possible implementations, the n-type thermoelectric dopant includes at least one of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole, cobalt diacene, and ruthenium diacene. These dopants all possess excellent n-type conductivity, i.e., electronic conductivity. The shell layer, through a combination of the thermoelectric polymer and the n-type thermoelectric dopant, enables electrons to transfer from the highest occupied orbital (HOMO) of the dopant to the lowest unoccupied orbital (LUMO) of the polymer, improving electron transfer efficiency. The resulting shell composite material exhibits high conductivity, further enhancing the conductivity of the modified phosphate-based cathode material.

[0083] In step S30 above, the phosphate-based active particles and the coating material are mixed in a liquid phase. In some possible implementations, this includes the step of: ultrasonically mixing the phosphate-based active particles and the coating material in an organic solvent for 2 to 3 hours in an inert atmosphere; so that the organic thermoelectric polymer and the n-type thermoelectric dopant in the coating material are uniformly and fully coated on the surface of the phosphate-based active particles.

[0084] In some possible implementations, the organic solvent used in the liquid-phase mixing step includes at least one of o-dichlorobenzene, toluene, xylene, and chlorobenzene. These organic solvents have good dispersibility for phosphate-based active particles and good solubility for organic thermoelectric polymers and n-type thermoelectric dopants in the coating material, which is beneficial for liquid-phase mixing between phosphate-based active particles and the coating material.

[0085] Among some possible implementations, solvent removal methods include solvent evaporation. While evaporating and removing the solvent, the coating material forms a uniform, consistent, complete, dense, and tightly bound shell on the surface of the phosphate-based active particles.

[0086] In some possible implementations, the solvent evaporation method involves removing the solvent under reduced pressure at 50°C–70°C, followed by drying under vacuum at 50°C–70°C. Under these conditions, solvent removal is beneficial for forming a shell of coating material on the phosphate-based active particles, without damaging the properties of the organic thermoelectric polymers and n-type thermoelectric dopants in the phosphate-based active particles and coating material. To ensure complete solvent removal, the processing time can be flexibly adjusted; complete solvent removal can be confirmed using infrared or proton nuclear magnetic resonance spectroscopy.

[0087] In other embodiments, the solvent removal method can be achieved by using rotary evaporation to remove the solvent and thus achieve coating.

[0088] In some possible implementations, the mass ratio of organic thermoelectric polymer to n-type thermoelectric dopant in the modified phosphate-based cathode material is 1:(0.07–0.2). This results in a better composite doping effect between the organic thermoelectric polymer and the n-type thermoelectric dopant in the shell, improving the ionic and electronic conductivity of the coated modified phosphate-based cathode material. Simultaneously, it enhances the compatibility between the organic thermoelectric polymer and the n-type thermoelectric dopant, ensuring uniform coating, density, and stability, and improving the compaction density, capacity, and stability of the modified phosphate-based cathode material.

[0089] In some possible implementations, the modified phosphate-based cathode material has a shell layer with a mass percentage of 3.3%–4.4% and a thickness of 3 nm–5 nm. In this case, the shell layer's coating thickness and content can achieve a complete, uniform, and stable coating effect on the phosphate-based active core, thereby improving the electrochemical properties of the modified phosphate-based cathode material, such as conductivity.

[0090] In some possible implementations, the D50 particle size of the modified phosphate-based cathode material is 500 nm to 2 μm. In this case, the smaller particle size of the modified phosphate-based cathode material shortens the ion migration path, which is beneficial for ion insertion and extraction during charge and discharge, thereby improving the rate performance and other electrochemical properties of the modified phosphate-based cathode material.

[0091] Thirdly, embodiments of this application provide a secondary battery, wherein the positive electrode sheet of the secondary battery contains the above-mentioned modified phosphate-based positive electrode material or the modified phosphate-based positive electrode material prepared by the above method.

[0092] The secondary battery provided in the third aspect of this application has the following characteristics: the positive electrode sheet of the secondary battery contains the above-mentioned modified phosphate-based positive electrode material. The modified phosphate-based positive electrode material is modified by a shell layer containing organic thermoelectric polymer and n-type thermoelectric dopant on its surface. It has the characteristics of good coating effect, high compaction density, high conductivity and ion mobility, and good structural and electrochemical performance stability. Therefore, it improves the electrochemical performance of the secondary battery, such as charge and discharge capacity and coulombic efficiency.

[0093] This application does not impose specific limitations on the materials and preparation methods of the positive electrode, negative electrode, electrolyte, separator, etc. in the secondary battery of the embodiments, and they can be obtained by any method that meets the application requirements.

[0094] In some possible implementations, the positive electrode of the secondary battery includes a current collector and an active layer formed on the surface of the current collector, the active layer containing the aforementioned modified phosphate-based positive electrode material.

[0095] In some possible implementations, the preparation of the active layer includes the following steps: mixing the above-mentioned modified phosphate-based positive electrode material, conductive agent and binder to form an electrode slurry, coating the electrode slurry onto the current collector, and then preparing the positive electrode sheet through steps such as drying, rolling and die cutting.

[0096] In some possible implementations, the mass percentage of modified phosphate-based cathode material in the active layer of the cathode sheet can be 90% to 95%. Specifically, the mass percentage of the modified cathode material in the cathode active material layer can be 90%, 91%, 92%, 93%, 94%, 95%, etc.

[0097] In some possible implementations, the current collector of the positive electrode includes, but is not limited to, any one of copper foil or aluminum foil.

[0098] In some possible implementations, the binder content in the positive electrode active material layer is 2wt%-5wt%. In specific embodiments, the binder content can be typical but not limited to 2wt%, 3wt%, 4wt%, 5wt%, etc.

[0099] In some possible implementations, the binder includes one or more of the following: polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethylcellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.

[0100] In some possible implementations, the conductive agent content in the positive electrode active material layer is 1wt%-5wt%. In specific embodiments, the conductive agent content can be a typical but not limited content such as 3wt%, 4wt%, or 5wt%.

[0101] In some possible implementations, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes.

[0102] In some possible implementations, the negative electrode active material of the secondary battery includes, but is not limited to, carbon materials such as graphite, soft carbon (e.g., coke), and hard carbon, or nitrides, tin-based oxides, tin alloys, and nano-anode materials. The current collector includes, but is not limited to, any one of copper foil and aluminum foil.

[0103] In some possible implementations, the steps for making the negative electrode sheet include: mixing the negative electrode active material with conductive agents such as conductive carbon black, binders such as carboxymethyl cellulose and styrene-butadiene rubber, and solvents such as water in a mass ratio of (80-99):(1-5):(2-10):100 to make a positive electrode mixed slurry, then degassing under vacuum, discharging the material, coating it on a coating machine, and obtaining the negative electrode sheet after rolling, slitting, and die-cutting.

[0104] In some possible implementations, the membrane is capable of blocking electrons while allowing ions to pass through. Exemplary membranes include, but are not limited to, at least one material selected from polypropylene fibers, polyacrylonitrile fibers, polyvinyl formal fibers, poly(ethylene glycol terephthalate), polyethylene terephthalate, polyamide fibers, and poly(p-phenylene terephthalamide).

[0105] In some possible implementations, the electrolyte comprises at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 At least one of SO2(N)[m, n], where m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte and do not undergo harmful side reactions with electrode materials, electrolyte, diaphragm, etc., and have good chemical stability.

[0106] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.

[0107] In some possible implementations, the battery cell types include lithium-ion batteries, as well as novel batteries such as lithium-air batteries and lithium metal batteries.

[0108] In some possible implementations, the battery cells of this application can be assembled into a battery module. The battery module can contain multiple battery cells, the specific number of which can be adjusted according to the application and capacity of the battery module. Furthermore, the battery module may also include a housing with a receiving space in which multiple battery cells are received.

[0109] In one possible implementation, battery cells and / or battery modules can also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0110] To enable those skilled in the art to clearly understand the above-described implementation details and operations of this application, and to demonstrate the significant improvement in the performance of the modified phosphate-based cathode material and its preparation method in the embodiments of this application, the above technical solutions are illustrated below through multiple embodiments.

[0111] Example 1

[0112] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0113] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0114] ② Preparation of organic thermoelectric polymer: 1.3 g of 4,9-dibromonaphthalimide with polyethylene glycol methyl ether substituents (three repeating ethylene glycol units), 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertival acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polynaphthalimide material. The reaction process is shown below:

[0115]

[0116] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the polynaphthalene diimide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and 0.05 g of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole was added. The mixture was stirred at 80 °C for 2 hours to dope the material and obtain the coating material.

[0117] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0118] Example 2

[0119] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0120] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0121] ② Preparation of organic thermoelectric polymer: 1.5 g of pyrrolopyrrole dione with polyethylene glycol methyl ether substituents (three repeating ethylene glycol units), 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertival acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polypyrrolopyrrole dione material. The reaction process is shown below:

[0122]

[0123] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the polypyrrolopyrrole dione material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and 0.05 g of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole was added. The mixture was stirred at 80 °C for 2 hours to dope the material and obtain the coating material.

[0124] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0125] Example 3

[0126] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0127] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0128] ② Preparation of organic thermoelectric polymer: 1.4 g of iso-indigo with polyethylene glycol methyl ether substituents as three repeating ethylene glycol units, 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertivalic acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polyiso-indigo material. The reaction process is shown below:

[0129]

[0130] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of polyisodimide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and 0.05 g of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole was added. The mixture was stirred at 80 °C for 2 hours to dope the material and obtain the coating material.

[0131] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0132] Example 4

[0133] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0134] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0135] ② Preparation of organic thermoelectric polymer: 1.5 g of pyrrolopyrrole dione with polyethylene glycol methyl ether substituents (three repeating ethylene glycol units), 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertival acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polypyrrolopyrrole dione material. The reaction process is shown below:

[0136]

[0137] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the polypyrrolopyrrole dione material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and 0.05 g of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole was added. The mixture was stirred at 80 °C for 2 hours to dope the material and obtain the coating material.

[0138] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0139] Example 5

[0140] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0141] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0142] ② Preparation of organic thermoelectric polymer: 1.4 g of iso-indigo with polyethylene glycol methyl ether substituents as three repeating ethylene glycol units, 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertivalic acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polyiso-indigo material. The reaction process is shown below:

[0143]

[0144] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of polyisodimide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and 0.05 g of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole was added. The mixture was stirred at 80 °C for 2 hours to dope the material and obtain the coating material.

[0145] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0146] Example 6

[0147] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0148] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0149] ② Preparation of organic thermoelectric polymer: 0.9 g of bisthiophene imide with polyethylene glycol methyl ether substituents as three repeating ethylene glycol units, 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertival acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain the bisthiophene imide material. The reaction process is shown below:

[0150]

[0151] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the bisthiophene imide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and 0.05 g of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole was added. The mixture was stirred at 80 °C for 2 hours to dope the material and obtain the coating material.

[0152] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0153] Example 7

[0154] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0155] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0156] ② Preparation of organic thermoelectric polymer: 1.3 g of 4,9-dibromonaphthalimide with polyethylene glycol methyl ether substituents (three repeating ethylene glycol units), 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertival acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polynaphthalimide material. The reaction process is shown below:

[0157]

[0158] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the polynaphthalene diimide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene, and ruthenium thiocene was added. 0.05g was mixed with water at 80℃ for 2 hours to obtain the coating material;

[0159] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain organic thermoelectric material coated and modified lithium iron phosphate cathode material.

[0160] Comparative Example 1

[0161] A carbon-coated modified lithium iron phosphate cathode material, the preparation of which includes the following steps:

[0162] 37.0 g of lithium carbonate, 241.9 g of iron nitrate, 115.0 g of ammonium dihydrogen phosphate, and 44.0 g of glucose were added to a ball mill and ground. The mixture was dry-ground for 2 hours and then wet-ground for 2 hours after the addition of ethanol to obtain a mixture. Under a nitrogen atmosphere, the precursor material was heated to 550°C at a heating rate of 5°C / min and sintered for 3 hours. Then, it was heated to 750°C at a heating rate of 5°C / min and sintered for 8 hours. Finally, it was cooled to room temperature at a cooling rate of 2°C / min to obtain carbon-coated modified lithium iron phosphate cathode material.

[0163] Comparative Example 2

[0164] An organic thermoelectric material-coated and modified lithium iron phosphate cathode material is prepared by the following steps:

[0165] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0166] ② Preparation of organic thermoelectric polymer: 1.6 g of 4,9-dibromonaphthalimide with carbon chain as substituent, 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tert-valerate were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polynaphthalimide material. The reaction process is shown below:

[0167]

[0168] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the polynaphthalene diimide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene and stirred at 80 °C for 2 hours to obtain the coating material;

[0169] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain lithium iron phosphate cathode material coated and modified with organic polymer material without n-type dopant.

[0170] Comparative Example 3

[0171] A lithium iron phosphate cathode material coated with an organic polymer material free of n-type dopants, the preparation of which includes the following steps:

[0172] ① Preparation of lithium iron phosphate cathode material: Take 37.0g of lithium carbonate, 241.9g of iron nitrate, and 115.0g of ammonium dihydrogen phosphate, add them to a ball mill jar for grinding, dry grinding for 2 hours, wet grinding for 2 hours after adding ethanol, to obtain a mixture; under a nitrogen atmosphere, heat the above precursor material to 550℃ at a heating rate of 5℃ / min and sinter for 3 hours; then heat to 750℃ at a heating rate of 5℃ / min and sinter for 8 hours; finally cool to room temperature at a cooling rate of 2℃ / min to obtain lithium iron phosphate cathode material;

[0173] ② Preparation of organic thermoelectric polymer: 1.3 g of 4,9-dibromonaphthalimide with polyethylene glycol methyl ether substituents (three repeating ethylene glycol units), 0.3 g of bithiophene, 17.7 mg of palladium chloride, 140.9 mg of tris(o-methoxyphenyl)phenylphosphine, 2.0 g of cesium carbonate, and 102.0 mg of tertival acid were placed in a glass container, and 20 mL of toluene was added under a nitrogen atmosphere. The reaction system was heated to 115 °C at a heating rate of 3 °C / min and reacted at this temperature for 48 hours. After cooling, the reaction solution was added to 500 mL of methanol to precipitate the material. After filtration, the precipitate was dried in a 45 °C oven for 12 hours to obtain polynaphthalimide material. The reaction process is shown below:

[0174]

[0175] ③ Preparation of coating material: Under a nitrogen atmosphere, 0.5 g of the polynaphthalene diimide material obtained in step ② was dissolved in 100 mL of o-dichlorobenzene and stirred at 80 °C for 2 hours to obtain the coating material;

[0176] ④ Coating treatment: Add 20g of lithium iron phosphate prepared in step ① to the coating material prepared in step ③, stir in an ultrasonic stirrer for 3 hours, heat the solution to 60℃ under reduced pressure and stir at the same time, and after most of the solvent is removed, place it in a vacuum drying oven and dry it under vacuum at 60℃ for 3 hours to obtain lithium iron phosphate cathode material coated and modified with organic polymer material without n-type dopant.

[0177] Furthermore, to verify the progressiveness of the embodiments of this application, the modified phosphate-based cathode materials prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0178] 1. X-ray diffraction tests were performed on the modified lithium iron phosphate cathode materials prepared in Examples 1-3, Example 7, and Comparative Examples 1-3, respectively. The XRD patterns of Examples 1-3 and Comparative Example 1 are attached. Figure 2 As shown, the XRD test patterns of Example 7 and Comparative Examples 2-3 are attached. Figure 3 As shown in the test images, the modified phosphate-based cathode materials prepared in Examples 1-3, Example 7, and Comparative Examples 1-3 of this application contain lithium iron phosphate, which corresponds to the lithium iron phosphate XRD standard card PDF#81-1173.

[0179] 2. The morphology of the uncoated modified lithium iron phosphate cathode material obtained in step ① of Example 1, and the modified lithium iron phosphate cathode materials prepared in Examples 1-3, Example 7, and Comparative Examples 1-3 were observed by scanning electron microscopy (SEM). The SEM image of the uncoated modified lithium iron phosphate cathode material in Example 1 is attached. Figure 4 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material in Example 1 is attached. Figure 5 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material in Example 2 is attached. Figure 6 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material in Example 3 is attached. Figure 7 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material in Example 7 is attached. Figure 8 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material of Comparative Example 1 is attached. Figure 9 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material of Comparative Example 2 is attached. Figure 10 As shown; the scanning electron microscope (SEM) image of the modified lithium iron phosphate cathode material of Comparative Example 3 is attached. Figure 11 As shown in the scanning electron microscope (SEM) results, the modified lithium iron phosphate cathode materials prepared in this application exhibit certain flocculent matter on the particle surface after organic thermoelectric material coating modification. No obvious flocculent matter was observed between the particles of the uncoated lithium iron phosphate cathode material obtained in step ① of Example 1 and the carbon-coated modified lithium iron phosphate cathode material of Comparative Example 1.

[0180] 3. The compaction density, D50 particle size, specific surface area, resistivity, etc. of the uncoated modified lithium iron phosphate cathode material prepared in step ① of Example 1, and the modified lithium iron phosphate cathode materials prepared in each example and comparative example were tested respectively.

[0181] ① Test method for compacted density: The test is conducted by applying a certain pressure to the powder;

[0182] ② Test method for D50 particle size: The powder particles are tested using a Malvern laser particle size analyzer;

[0183] ③ Specific surface area test method: Tested using a Micron 3020 physical adsorption instrument;

[0184] ④ Resistivity test method: Tested using a two-probe contact resistance tester;

[0185] The test results are shown in Table 1 below:

[0186] Table 1:

[0187]

[0188] As can be seen from the above test results, the modified phosphate-based cathode material prepared in the embodiments of this application has a larger compaction density, lower resistivity, and suitable particle size and specific surface area.

[0189] 4. The modified phosphate-based cathode materials prepared in the above embodiments and comparative examples are applied to lithium-ion batteries. The specific preparation steps are as follows:

[0190] (1) Preparation of slurry: The positive electrode materials prepared in the above examples and comparative examples were added to an agate ball mill jar with a volume of 500 mL, along with 23.3 g of superconducting carbon black (SP) and 0.12 g of binder polyvinylidene fluoride (PVDF). Then, 16 mg of solvent N-methylpyrrolidone (NMP) was added, and the slurry was obtained by ball milling at a speed of 360 rpm for 4 h.

[0191] (2) Coating of slurry: Adjust the scale of the scraper of the coating machine, and evenly coat the slurry after ball milling onto the aluminum foil. Place the coated electrode in a vacuum drying oven at 130°C and bake for 3 hours.

[0192] (3) Rolling and stamping: Place the aluminum foil coated with slurry flat in the middle of the roller and roll it to press the electrode sheet; then press the front of the rolled electrode sheet tightly against the perforated area and stamp it in sequence; the compaction density of the electrode sheet is controlled at 2.0~2.4g / cm³. 3 The diameter is 14mm and the thickness is 0.05~0.10mm; the punched electrode is placed in a vacuum drying oven at 130℃ and baked for 3 hours;

[0193] (4) Assemble the button cell in the glove box in the following order: negative electrode shell, spring, steel sheet, lithium sheet, separator, positive electrode sheet and positive electrode shell. During the process, inject 10 μL of electrolyte. Then use a sealing machine to seal the button cell. The assembled button cell is used for subsequent electrochemical performance testing.

[0194] The coin cells prepared in the above embodiments and comparative examples were tested for their 0.1C discharge capacity, 0.1C charge capacity, 0.1C coulombic efficiency, 1C discharge capacity, 1C charge capacity, and 1C coulombic efficiency. The test results are shown in Table 2 and Appendix. Figures 12-15 As shown:

[0195] Table 2

[0196]

[0197] As can be seen from the above test results, the modified phosphate-based cathode material prepared in this application embodiment exhibits higher charge and discharge capacity and coulombic efficiency when applied to a lithium-ion battery system. The 0.1C coulombic efficiency is higher than 98.12%, and the 1C coulombic efficiency is higher than 84.65%.

[0198] The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A modified phosphate-based cathode material, characterized in that, It includes a phosphate-based active core and a shell covering the outer surface of the core. The shell comprises an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant. The organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, and the electron-withdrawing conjugated units contain alkoxy-substituted chains. The phosphate-based active core includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium nickel phosphate. The electron-withdrawing conjugated unit includes at least one of the following: 4,9-dibromonaphthalene diimide unit, pyrrolopyrrole dione unit, isoindigo unit, and thiophene diimide unit; The electron-donating unit includes at least one of the following: a dithiophene unit, a bisthiophene unit, a thiophene unit, a selenophene unit, and a furan unit; The n-type thermoelectric dopant includes at least one of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole, cobalt diaceticate, and ruthenium diaceticate; The alkoxy-substituted chain includes at least one of polyethylene glycol ether-substituted chains and polyethylene glycol ester-substituted chains.

2. The modified phosphate-based cathode material as described in claim 1, characterized in that, In the organic thermoelectric polymer, the electron-withdrawing conjugated units and the electron-donating units are repeated alternately. And / or, the modified phosphate-based cathode material further includes the free organic charge transfer complex.

3. The modified phosphate-based cathode material as described in claim 2, characterized in that, The organic thermoelectric polymer includes at least one of the following: polypyrrolopyrrole dione with alkoxy-substituted chains, polybisthiophene imide with alkoxy-substituted chains, polyisoindigo with alkoxy-substituted chains, and polynaphthalene diimide with alkoxy-substituted chains. And / or, the number-average molecular weight of the organic thermoelectric polymer is 70 kDa to 100 kDa; And / or, the alkoxy-substituted chain includes a polyethylene glycol methyl ether substituted chain; And / or, the number of repeating units of ethylene glycol in the alkoxy-substituted chain is 3 to 12; And / or, the mass ratio of the organic thermoelectric polymer to the n-type thermoelectric dopant is 1:(0.07~0.2).

4. The modified phosphate-based cathode material according to any one of claims 1 to 3, characterized in that, In the modified phosphate-based cathode material, the shell layer has a mass percentage content of 3.3% to 4.4%. And / or, in the modified phosphate-based cathode material, the thickness of the shell layer is 3nm to 5nm; And / or, the D50 particle size of the modified phosphate-based cathode material is 500 nm to 2 μm.

5. A method for preparing a modified phosphate-based cathode material, characterized in that, Includes the following steps: Provide phosphate-based active particles; the phosphate-based active particles include at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium nickel phosphate; A coating material is provided, comprising an organic charge transfer complex formed by an organic thermoelectric polymer and an n-type thermoelectric dopant, wherein the organic thermoelectric polymer contains electron-withdrawing conjugated units and electron-donating units, the electron-withdrawing conjugated units containing alkoxy-substituted chains; the electron-withdrawing conjugated units include at least one of 4,9-dibromonaphthalenediimide units, pyrrolopyrroledione units, isoindigo units, and thiophene imide units; the electron-donating units include at least one of bithiophene units, bisthiophene units, thiophene units, selenophene units, and furan units; the n-type thermoelectric dopant includes at least one of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole, cobalt diacetene, and ruthenium diacetene; and the alkoxy-substituted chains include at least one of polyethylene glycol ether substituted chains and polyethylene glycol ester substituted chains. After mixing the phosphate-based active particles and the coating material in the liquid phase, the solvent is removed so that the coating material coats the outer surface of the phosphate-based active particles to form a shell layer, thereby obtaining a modified phosphate-based cathode material.

6. The method for preparing the modified phosphate-based cathode material as described in claim 5, characterized in that, The preparation of the organic thermoelectric polymer includes the following steps: in an inert atmosphere, an electron-withdrawing conjugated monomer, an electron-donating monomer, a catalytic system and an organic solvent are mixed and heated to react, and the organic thermoelectric polymer is obtained by separation. And / or, the preparation steps of the coating material include: dissolving the organic thermoelectric polymer and the n-type thermoelectric dopant in an organic solvent in an inert atmosphere, and then mixing them at a temperature of 65℃~85℃ for 0.5h~2h to obtain the coating material; And / or, the liquid phase mixing step includes: ultrasonically mixing the phosphate-based active particles and the coating material in an organic solvent for 2-3 hours in an inert atmosphere; And / or, the method for removing the solvent includes solvent evaporation.

7. The method for preparing the modified phosphate-based cathode material as described in claim 6, characterized in that, The molar ratio of the electron-withdrawing conjugated monomer to the electron-donating monomer is 1:(1.0~1.2). And / or, the catalytic system includes a metal catalyst, a catalyst complexing agent, an alkali metal salt, and pivalic acid; And / or, the temperature conditions for the heating reaction are 110℃~120℃, and the duration is 24h~48h; And / or, the organic solvents used in the steps of preparing the organic thermoelectric polymer, preparing the coating material, and the liquid phase mixing each independently include at least one of o-dichlorobenzene, toluene, xylene, and chlorobenzene; And / or, the solvent evaporation method includes the following steps: removing the solvent under reduced pressure at a temperature of 50°C to 70°C, followed by drying under vacuum at a temperature of 50°C to 70°C.

8. The method for preparing the modified phosphate-based cathode material as described in claim 7, characterized in that, The organic thermoelectric polymer includes at least one of the following: polypyrrolopyrrole dione with alkoxy-substituted chains, polybisthiophene imide with alkoxy-substituted chains, polyisoindigo with alkoxy-substituted chains, and polynaphthalene diimide with alkoxy-substituted chains. And / or, the number-average molecular weight of the organic thermoelectric polymer is 70 kDa to 100 kDa; And / or, the alkoxy-substituted chain includes a polyethylene glycol methyl ether substituted chain with a repeating number of 3 to 12 ethylene glycol units; And / or, in the modified phosphate-based cathode material, the mass ratio of the organic thermoelectric polymer to the n-type thermoelectric dopant is 1:(0.07~0.2). And / or, in the modified phosphate-based cathode material, the shell layer has a mass percentage content of 3.3%~4.4% and a thickness of 3nm~5nm; And / or, the D50 particle size of the phosphate-based active particles is 500 nm to 2 μm.

9. A secondary battery, characterized in that, The positive electrode of the secondary battery contains a modified phosphate-based positive electrode material as described in any one of claims 1 to 4, or a modified phosphate-based positive electrode material prepared by the method described in any one of claims 5 to 8.

Citation Information

Patent Citations

  • Squaric acid-based polymers, their manufacturing processes and their uses

    CN112041370A

  • Bis(pyridinium)-naphthalene diimide redox ionic compounds as electrode active materials

    US20200028172A1